Identifying Pre-Dorset structural features on southern Baffin Island: Challenges and considerations for alternative sampling methods - Milne, S. (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2003)
AbstractThis paper describes an isolated Pre-Dorset component found at the Tungatsivvik (KkDo-3) site on southern Baffin Island. Micro-debitage analysis and systematic core sampling are proposed as a combined strategy to facilitate future investigations of Pre-Dorset occupations in this region.